Ontology, Epistemology, and Axiology of Project-Based Learning - Triyani, Desi; Anwar, Miftahulkhairah; Nuruddin, Nuruddin (Proceeding International Conference on Religion, Science and Education, 2024)
Considering ontology, epistemology, and axiology in planning and implementing project-based learning is important. This helps to ensure that projects are undertaken with a clear understanding of the objects studied, the methods used, and relevant value considerations. Using theoretical studies, ontology, epistemology, and axiology are applied to project-based learning in senior high schools for Indonesian language lessons.